Carceral Logics Human Incarceration and Animal Captivity - Gruen, Lori; Marceau, Justin (Social Sciences, 2022)
In this volume, Lori Gruen and Justin Marceau invite experts to examine connections between mass incarceration of humans and captive control of animals. Chapters explore how carceral responses to animal crime and carceral thinking about animal captivity can impact the lives and legal status of both humans and non-humans.